Metasomatism and REE mineralization of the Zilair Formation sedimentary rocks in the Khudolaz complex gabbro massif exocontact zone (Chebarkul area, Southern Urals) - Evgeny I. Mikheev; Ildar R. Rakhimov; Elena O. Shaparenko; Elena I. Soroka (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. West-Magnitogorsk zone (Southern Urals) hold a lot of Early Carboniferous gabbroic and granitoid intrusions which associated with various mineralization types (Ti-Fe, Cu-Ni-PGE, Au), but information about REE mineralization is scarce. Contact hydrothermal-metasomatic processes rarely form the economic REE mineral deposits, but they can provide valuable information about the behaviors of rare earth elements. Aim. Mineralogical and geochemical characteristics of metasedimentary rocks from exocontact zone of the Khudolaz complex gabbro massif, study of rare earth minerals, determination of the formation conditions and sources of mineralizing fluids. Methods. Minerals were studied using optical and scanning electron microscopy; the bulk composition of the rocks was determined by XRF and ICP-MS analytical techniques; vapor-liquid fluid inclusions in calcite were studied using microthermometry and Raman spectroscopy; the isotopic composition of carbon and oxygen was determined for metasedimentary silicate-carbonate metasomatites. Results and conclusions. In the Khudolaz complex gabbro massif exocontact zone, the Zilair Formation sedimentary rocks undergo recrystallization associated with hydrothermal-metasomatic processes and manifested as the formation of globular and granoblastic textures, stylolites, the formation of metacrystals of various rock-forming and accessory minerals, including rare earth minerals (synchisite-(Ce), CaCe(CO3)2F, and REE-rich clinozoisite, (Ca,REE)2Al3O[Si2O7][SiO4](OH)). According to microthermometry of vapor-liquid fluid inclusions in calcite, the formation of REE-bearing minerals occurred at temperatures not lower than 150 °С. The sources of rare earth elements could be both the Zilair Formation sedimentary rocks and gabbro, as evidenced by the increase in REE concentrations and isotopic composition of oxygen and carbon in silicate-carbonate metasomatites (δ18OSMOW =13.80…15.98 ‰, δ13С = –5.64…–2.18).